The impact of communication skills and emotional intelligence on employee performance through organizational citizenship behavior as mediation - Melvina, Via; Marumpe, Dody Pratama; Daud, Ilzar; Mufrihah, Mazayatul (Nur Science Institute, 2024)
This study aims to find out how communication skills and emotional intelligence affect the performance of Alfamart employees in West Kalimantan. This study explores the potential role of mediating Organizational Citizenship Behaviour in this relationship. This work uses the Structural Equation Model (SEM) to analyse the data using Smart PLS 4.0 software. This study integrates mediating variables and investigates the relationship between independent and dependent variables to provide empirical support for hypotheses. As part of the data collection strategy for this study, 214 Alfamart employees in the West Kalimantan region were given questionnaires. The study results show that organisational, civic behaviour, emotional intelligence, and communication skills positively and significantly influence worker performance. However, organisational citizenship behaviour only mediates communication skills; It does not link emotional intelligence to employee success.